1996
DOI: 10.1037/0008-400x.28.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of knowledge transformational reports while children write narratives.

Abstract: Bereiter and Scardamalia (1987) proposed a model of children's writing, labeled "knowledge-telling," which they characterized as being simple and linear in nature. By contrast, their model of more expert writing is described as "knowledge transformational," because it is more sophisticated in its involvement of complex problem-solving processes. These researchers report that children, and even most adolescents, do not write at a level that would implicate knowledge-transformational processes, especially in exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In this respect, a major limitation of the present study is that we measured students' applied writing strategies solely by means of self‐report questionnaires. Indeed, previous research has indicated that novice writers often fail to plan their text in advance (Cameron & Moshenko, ), have difficulties with generating sentences fluently (McCutchen et al., ), and poorly revise their text by focusing on surface‐level aspects (McCutchen et al., ). In the present study, however, students reported rather high levels of thinking, planning, revision, and control strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, a major limitation of the present study is that we measured students' applied writing strategies solely by means of self‐report questionnaires. Indeed, previous research has indicated that novice writers often fail to plan their text in advance (Cameron & Moshenko, ), have difficulties with generating sentences fluently (McCutchen et al., ), and poorly revise their text by focusing on surface‐level aspects (McCutchen et al., ). In the present study, however, students reported rather high levels of thinking, planning, revision, and control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with students in the lower grades, the automation of basic writing skills is increased, enabling upper elementary students to engage in higher order writing skills and strategies (e.g., revising; Berninger et al., ). Previous research, however, has showed that applying these higher order writing skills remains cognitively challenging for this age group, as they often fail to prewriting planning (Cameron & Moshenko, ), have difficulties with generating sentences fluently (McCutchen, Covill, Hoyne, & Mildes, ), and poorly revise their text by focusing mainly on surface‐level aspects (e.g., spelling; McCutchen, Francis, & Kerr, ).…”
mentioning
confidence: 99%
“…Students who do not receive instruction in advanced planning spend little time planning before writing (De La Paz, 1997;Scardamalia & Bereiter, 1986). A considerable amount of instructional support is necessary to teach children how to plan conceptually in order to improve the quality of written text (Cameron & Moshenko, 1996;De La Paz & Graham, 2002;Page-Voth & Graham, 1999). While evidence supports the importance of learning advanced planning skills in writing development, less is known about whether overall time allocated to planning instruction or the specific instructional practices are more closely related to increased writing quality.…”
Section: Instructional Predictors Of Student Achievementmentioning
confidence: 99%
“…Although planning is an important part of the writing process (Hayes & Flower, ), young children typically do not devote much time to planning (Bereiter & Scardamalia, ). In fact, Cameron and Moshenko () found the “start‐−−up time” (i.e., planning time) of 53 sixth graders to be between 15 seconds and 387 seconds, with the average being just over two minutes. Similarly, fifth and sixth graders identified with lear−ning disabilities spent less than one minute planning, even though they were prompted to plan before writing and encouraged to take as much time as needed to do so (MacArthur & Graham, ).…”
Section: Collecting Ideas In a Notebookmentioning
confidence: 99%